Electrochemistry of metalloproteins - Oliver, B; Oliver, B. Nigel (1985)
﻿ The direct (unmediated) electrochemistry of a variety of redox proteins has been studied at a range of electrode materials. Electrochemical studies using cytochromes, iron-sulphur proteins and copper proteins show a marked enhancement of the heterogeneous electron-transfer rate at the "edge" plane of pyrolytic graphite. Parallel ESCA studies have shown that mechanical polishing of edge graphite provides an electrode with a high surface coverage of oxidised functional groups. These results indicate the importance of oxidised functional groups in facilitating productive interactions with the proteins. The importance of multivalent cations has also been established. For proteins with negatively-charged physiological interaction domains, such as plastocyanin or 2[4Fe-4S] ferredoxin, elect reactivity at "edge"-oriented graphite is promoted and stabilised in the presence of multivalent cations such as Cr(NH,sub>3 )63+. On the other hand, the electrochemistry of positively-charged cytochrome ̲c is inhibited and destabilised in the presence of such cations. Promotion and inhibition profiles for a range of proteins, together with various cations, indicate the participation of specific electrode-cation-protein interactions. Studies on plastocyanin, whose electrochemistry is troubled by a time-dependent deterioration of response, have demonstrated the importance of low protein concentration, low pH, low temperatures (3°C) and, in particular, Pt(NH3)64+ at stabilising faradaic responses. Surface modification of edge pyrolytic graphite has been achieved electrochemically by exploiting the contrasting substitutional reactivity of chromium(III) and chromium(II). The modified-surface, incorporating chromium(III) complexes, promoted reversible direct electrochemistry of plastocyanin. The direct electrochemistry of plastocyanin, at pH 4, has provided an insight into the possible importance of a kinetically-inactive protonated form of the reduced protein. The t1/2 for deprotonation of Cu(I)-plastocyanin is estimated to be < 1 ms. Finally, the direct electrochemistry of azurin was exploited in the design of an electrocatalytic system. The electrochemical oxidation of p-cresol to p-hydroxybenzaldehyde was effected enzymically.